2012
DOI: 10.1371/journal.pone.0037757
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate-Induced Modulation of Hepatic Molecular Mechanisms: An Aspect for Its Anti-Insulin Resistant Effect

Abstract: Topiramate is an antiepileptic drug known to ameliorate insulin resistance besides reducing body weight. Albeit liver plays a fundamental role in regulation of overall insulin resistance, yet the effect of topiramate on this organ is controversial and is not fully investigated. The current work aimed to study the potential hepatic molecular mechanistic cassette of the anti-insulin resistance effect of topiramate. To this end, male Wistar rats were fed high fat/high fructose diet (HFFD) for 10 weeks to induce o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…Aminotransferases are indicators of hepatic health that is compromised in case of obesity, IR and diabetes [75]. Moreover, fatty changes are associated with the increased level of TNF-α, proven to increase in this model [19], which has a great influence on ALT elevation. Therefore, activated aminotransferases may reflect the role of hepatic gluconeogenesis and/or inflammation in the type 2 diabetes pathophysiology.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Aminotransferases are indicators of hepatic health that is compromised in case of obesity, IR and diabetes [75]. Moreover, fatty changes are associated with the increased level of TNF-α, proven to increase in this model [19], which has a great influence on ALT elevation. Therefore, activated aminotransferases may reflect the role of hepatic gluconeogenesis and/or inflammation in the type 2 diabetes pathophysiology.…”
Section: Discussionmentioning
confidence: 86%
“…These aliquots were used for the estimation of adiponectin receptor 1 and 2 (Adipo R1 & R2) [19], glucose transporter 2 and 4 (GLUT 2 & 4) and myeloperoxidase (MPO) activity, using the corresponding ELISA rat kit (Uscn, Wuhan, China; EIAab, Wuhan, China and Hycult biotech, Uden, Netherlands, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Topiramate (TPM), which is a sulfamate-substituted monosaccharide, is used in neurotherapy for the management of epilepsy and migraine (9). It is documented to possess weight-reducing properties in addition to insulin resistance-improving effects (10,11). It has been demonstrated that TPM decreases TNF-α and oxidative stress in addition to being an effective antioxidant (11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…It is documented to possess weight-reducing properties in addition to insulin resistance-improving effects (10,11). It has been demonstrated that TPM decreases TNF-α and oxidative stress in addition to being an effective antioxidant (11,12,13). The inhibition of TNF-α release or its neutralization with anti-TNF-α antibodies decreases the number of neutrophils infi ltrating the kidney and reduces I/R injury (14).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress causes production of abnormal cytokine production (TNF- and IL-6) 25 . TNF- not only increases adipocyte lipolysis but also has adverse effects on the insulin signaling pathway through changing the tyrosine/serine phosphorylation of insulin receptor substrate 26 . CRP is a key inflammatory factor that is regulated by IL-6, IL-1, and TNF-α, and produced by the liver in response to inflammation 27 .…”
Section: Discussionmentioning
confidence: 99%